PENGARUH INFEKSI Escherichia coli MELALUI BERBAGAI RUTE TERHADAP GAMBARAN ERITROSIT, HEMOGLOBIN, DAN PCV AYAM BROILER - , CITRA KUSUMA WARDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Colibacillosis is a common disease in chicken. This disease caused negative effect and economic loss in chicken farming. This study was aiming to determine the effect of Escherichia coliinfection via intratracheal, oral, intravenous, intramuscular, and cloacal to determine the number of erythrocytes, hemoglobin, and packed cell volume (PCV) of four weeks old broilerâs blood. This study used 18 chickens were divided into one control group and five treatment groups, that were intratracheal, oral, intravenous, intramuscular, cloacal, each group consist three chickens. Bacteria that used for infection was avian pathogenic Escherichia coliat a dose of 10 8 cell/ml. Blood sampling were taken before infection and 14 days after infection. Statistical analysis by two-way ANOVA showed a significant effect (r< 0.05) of E. coliinfection to the total number of erythrocytes, hemoglobin, and packed cell volume (PCV). Escherichia coliinfection pathway didnât give significant effect (r> 0.05) to the total number of erythrocytes and hemoglobin level, but significantly different (r< 0.05 ) to the PCV value. Statistical analysis by the Multiple Comparison Analysis (MCA) showed intravenous pathway value 30,8333 which was the most effective to cause changes in PCV value. The decrease in the averages of the total number of erythrocytes,hemoglobin level, and PCV value in circulation is an indication of anemia due to nutritional deficiencies and as a result of hemolytic due to E. coliinfection.